El paisaje cultural y el desarrollo local, un ensayo de aproximación - Rosas Williams, Jessica María (2016)
The present essay constitutes an initial proposal for a reflection about local development management in territory, incorporating the discipline of landscape study. As long as it presents itself as a useful tool in the task of articulating the wide spectrum of knowledge necessary for an integral understanding of local realities, in accordance with the latest trends in the sustainable management of territories, basic definitions are explored, initial terms of the proposal defined and provisional conclusions presented.